2020
DOI: 10.1021/acs.macromol.0c01303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ionomer Loading and Substrate Wettability on the Morphology of Ionomer Thin Films Using Coarse-Grained Solvent Evaporation Simulations

Abstract: Coarse-grained molecular dynamics simulations were performed to understand the evolution of ionomer morphologies in solutions during solvent evaporation. To reproduce experimental fabrication conditions, the simulation conditions, such as evaporation and sedimentation rate, were determined based on a dimensionless parameter, the Péclet number, providing a direct link between simulation results and experimental findings. The effects of ionomer loading and substrate wettability on the morphologies of ionomer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…The hydrophobic backbones tend to interact with the non-polar solid phase, so the polar ionic groups tend to point towards the polar liquid phase and promote wettability. 186 On the other hand, the ionic groups can also re-orient towards the polar surfaces of the solid phase instead of the liquid phase, leaving the hydrophobic backbones exposed to the water phase. In this case, the ionomer in the CL promotes hydrophobicity.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…The hydrophobic backbones tend to interact with the non-polar solid phase, so the polar ionic groups tend to point towards the polar liquid phase and promote wettability. 186 On the other hand, the ionic groups can also re-orient towards the polar surfaces of the solid phase instead of the liquid phase, leaving the hydrophobic backbones exposed to the water phase. In this case, the ionomer in the CL promotes hydrophobicity.…”
Section: Carbon-based Materialsmentioning
confidence: 99%
“…The direct evidence for the isolated water has been not obtained at the moment but must be due to the effects of the thin film structure of Nafion in the wet CL. As predicted by a computer simulation, the thin film fluctuates in thickness, leading to deformation of the ionomer clusters. This deformation may produce some isolated water regions.…”
Section: Results and Discussionmentioning
confidence: 82%
“…In addition to the SANS results, it is observed that the Nafion thin film fluctuates in thickness from the computer simulation results. 25 Based on the results, a schematic drawing is shown for the structure of the wet CL in the upper part of Figure 9.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Martini has been applied to model ion‐conducting polymeric materials used as ion‐exchange membranes for fuel cell applications. [ 210,220–226 ] Proton‐exchange‐membrane fuel cells use acid polyelectrolytes, such as Nafion, as the membrane material. The membranes are formed by solution‐processing techniques.…”
Section: Example Applicationsmentioning
confidence: 99%